SISTEM PELAYANAN DI LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (LPPM) UNIVERSITAS SAHID SURAKARTA BERBASIS WEB - Ratmawati, Nurul Pradana; Susilo, Dahlan; Retnoningsih, Dwi (JURNAL GAUNG INFORMATIKA, 2014)
Information systems research and community service institute (LPPM) Sahid. Surakarta University is an institution that has the task to coordinate, monitor and evaluate the implementation of research activities and public service organized by the lecturers who performed in groups or individually. LPPM website already exist, the previous design of the website can be accessed by four users are admin, lecturers, students and visitors then it can be implemented for lecturers and students. In this research researchers completed the admin in order to provide information to visitors and adds reviewers to evaluate the proposal. Data collection methodologyused is the method of observation, and the design methods, the experimental method. The conclusion LPPM website has been tested by the method of McCall and got atotal value of 75.8% quality. According to the results of the test are expected to be applied to the LPPM website USAHID Surakarta to help provide the latest informationand online data processing.